On Interpreting the Random Walk Behavior of Nominal and Real Exchange Rates - Adams, Charles (IMF Working Papers; Working Paper ;, 1991)
The random walk property of exchange rates is frequently regarded as carrying strong implications for the kinds of shocks that have driven exchange rates and the models appropriate for analyzing their behavior. This paper conducts stochastic simulations of Dornbusch's (1976) sticky-price monetary model, calibrated for representative parameter values for the United States. It shows that the model is capable of generating time series for both real and nominal exchange rates that are statistically indistinguishable from random walks when all shocks are nominal.